Strategi Pemberdayaan Kader dengan Deteksi Dini pemeriksaan IVA dan Do IVA di Desa Limus Nunggal Bogor - Nur Aini; Yocki Yuanti; Yulia Herawati (Universitas Baiturrahim, 2026)
Cervical cancer is one of the leading causes of death in women after breast cancer. Low coverage of early detection through VIA and Do IVA tests remains a problem, primarily due to a lack of public knowledge. This situation requires an increased role for community health workers in education and health promotion related to early cervical cancer detection. This Community Service activity aims to enhance the role and capacity of community health workers in providing education and supporting the implementation of VIA and Do IVA tests. The methods used include training, counseling, and the implementation of VIA and Do IVA tests. The activity involved 20 community health workers. Results showed an increase in community health workers' knowledge from an average of 72.52 to 85.00, the formation of a VIA test team, and the development of the ivacenterlimus website as a communication tool between the community and community health workers. This activity is expected to increase community health workers' involvement and expand the reach of cervical cancer early detection in the community.